2022
DOI: 10.1038/s41598-022-14012-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns and climate drivers of malaria in three border areas of Brazil, Venezuela and Guyana, 2016–2018

Abstract: In 2020, 77% of malaria cases in the Americas were concentrated in Venezuela, Brazil, and Colombia. These countries are characterized by a heterogeneous malaria landscape and malaria hotspots. Furthermore, the political unrest in Venezuela has led to significant cross-border population movement. Hence, the aim of this study was to describe spatial patterns and identify significant climatic drivers of malaria transmission along the Venezuela-Brazil-Guyana border, focusing on Bolivar state, Venezuela and Roraima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Of the total of 52 studies, 26 (50.0%) were on infectious diseases, 11 (21.1%) on malaria [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], 8 (15.3%) on Dengue fever [ 40 , 41 , 42 , 43 , 44 , 45 ], 4 (7.6%) on HIV [ 46 , 47 , 48 , 49 ], and 3 (5.7%) on TB [ 50 , 51 , 52 ]. Overall, 10 (19.2%) studies were on chronic diseases [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], 8 (15.5%) on maternal and child health [ 63 , 64 , 65 , 66 ], 3 (5.7%) on nutrition [ 67 , 68 , 69 ] and 5 (9.6%) were applied to other health-related outcomes [ 58 , 70 , 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the total of 52 studies, 26 (50.0%) were on infectious diseases, 11 (21.1%) on malaria [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], 8 (15.3%) on Dengue fever [ 40 , 41 , 42 , 43 , 44 , 45 ], 4 (7.6%) on HIV [ 46 , 47 , 48 , 49 ], and 3 (5.7%) on TB [ 50 , 51 , 52 ]. Overall, 10 (19.2%) studies were on chronic diseases [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], 8 (15.5%) on maternal and child health [ 63 , 64 , 65 , 66 ], 3 (5.7%) on nutrition [ 67 , 68 , 69 ] and 5 (9.6%) were applied to other health-related outcomes [ 58 , 70 , 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 10 (19.2%) studies were on chronic diseases [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], 8 (15.5%) on maternal and child health [ 63 , 64 , 65 , 66 ], 3 (5.7%) on nutrition [ 67 , 68 , 69 ] and 5 (9.6%) were applied to other health-related outcomes [ 58 , 70 , 71 , 72 , 73 ]. Most of the studies (42, 80.7%) used an ecological study design [ 30 , 31 , 33 , 34 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 51 , 52 , 53 , 54 , 55 , 56 , 58 , 59 , 60 , 61 , 62 , 64 , 65 , 66 , 67 , 69 ,…”
Section: Resultsmentioning
confidence: 99%
“…While not directly a mechanism for transmission for LF, standing water remains a key component in the life cycle of Culex . quinquefasciatus [ 2 ], and an important risk factor for numerous other diseases affecting people living in the area [ 37 ]. Whether this association with increased participation in the MDA indicates a misattribution of disease risks communicated in other public health campaigns—or the association is simply a spurious significance—future studies should consider the influence of competing messaging campaigns or, if possible, include a more substantive qualitative component to investigate these associations.…”
Section: Discussionmentioning
confidence: 99%
“…In South-West China, precipitation value of 26 mm found to be positively associated with malaria infection after 2–4 months ( 77 ). While for a study done in Brazil, Guyana and Venezuela showed that malaria infection decreased by 1.6% per 1 cm increase in 6 months lagged precipitation ( 79 ). In Indonesia, a 1 mm increase in precipitation was associated with a 0.08% increase of malaria infection at lag of 3 months ( 76 ).…”
Section: Discussionmentioning
confidence: 99%